NAMES AND TERMS OF LIVELIHOOD OF SUNDANESE PEOPLE: AN ETHNOLINGUISTIC STUDY: NAMA DAN ISTILAH MATA PENCAHARIAN MASYARAKAT SUNDA: SEBUAH KAJIAN ETNOLINGUISTIK - Danan Darajat; Agus Suherman (LLDIKTI Wilayah X, 2021)
Livelihood is one of the cultural institutions. The names and terms contained in it, especially in Sundanese land, are now rarely known by the people. Therefore, it is necessary to conduct studies from an ethnolinguistic point of view. By using descriptive methods and library study techniques, this paper aims to inventory the names and livelihood terms of Sundanese people, both public livelihoods (which are often done) and livelihoods documented in the ancient Sundanese manuscript Sanghyang Siksa Kandang Karesian (SSKK) which was completed in 1518 AD. The results showed that the names and livelihood terms of Sundanese people are very diverse, ranging from ngahuma (farming), nyawah (farming in rice fields), nyadap (tap aren), dagang (trading), dalang (puppet show artist), paraguna (karawitan expert), hempul (traditional game expert), juru pantun (pantun performance artist), painter, panday (ironsmith), ma-rangguy (carvers), catra (cook/chef), pangeuyeuk (textile expert), pratanda (religious expert), hulujurit (warlord/warlord), brahminana (brahmana), ja(ng)gan (monk), bujangga (astrologer), pandita (priest/smart man), queen (leader/president), mangkubumi (deputy head of state), puhawang (skiper), byapari (mathematician/itung-itungan), paraloka (priest/monk), and juru basa darmamurcaya (linguist). This indicates that Sundanese people have been able to do various types of work and at the same time show that the language used by the community is able to record various activities that they do.